PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA GURU YANG DIMODERASI GAYA KEPEMIMPINAN TRANSFORMASIONAL DI SMA NEGERI SE KABUPATEN REMBANG TAHUN 2015 - Happy Purwanto, 1352020052; Sri Mindarti, Ceacilia (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze Influence of Work Motivation and Discipline Against Teacher Performance Moderated Transformational Leadership Styles On High Schools Teachers in District Rembang. In this study population of all teachers in the district of Rembang on High Schols Â servants, while the sample used as many as 194 respondents with a sampling technique. With the criteria of the respondents are civil servants Teachers in High Schools in Kabupaten Rembang. Measurements using a Likert scale with 5 (five) alternative answers. Test instrument used is the validation and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Motivation positive and no significant impact on teacher performance, (ii) Work Discipline positive and no significant impact on teacher performance, (iii) the Transformational leadership style has weakens effect on teacher performance, (iv) transformational StyleÂ leadership has weakens and no significant effect on work motivation against performance Teachers, (v) the principals leadership style transformasional had no effect on performanceÂ Work Discipline Master.Keywords: Work Motivation, Work Discipline, Performance Teacher, and Transformationall Leadership Styles